An experimental evaluation of the benefits and costs of providing fertility information to adolescents and emerging adults. Issue 7 (17th May 2018) - Boivin, J; Koert, E; Harris, T; O'Shea, L; Perryman, A; Parker, K; Harrison, C
Abstract: STUDY QUESTION: Does the provision of fertility (compared to control) information affect fertility-related knowledge, perceived threat of infertility, anxiety, physical stress and fertility plans in adolescents and emerging adults? SUMMARY ANSWER: The provision of fertility information was associated with increased fertility knowledge (emerging adults) and greater infertility threat (adolescents and emerging adults). WHAT IS KNOWN ALREADY: According to fertility education research, adolescents and emerging adults know less than they should know about fertility topics. Fertility knowledge can be improved through the provision of information in older adults. STUDY DESIGN, SIZE, DURATION: Experimental design. Secondary and university students completed pre-information questionnaires, were randomly assigned via computer to an experimental group, read either fertility (FertiEduc group) or healthy pregnancy information (Control group), and completed post-information questionnaires. Data were collected in group sessions via an online portal. PARTICIPANTS/MATERIALS, SETTING, METHODS: Eligible participants were aged 16–18 (adolescents) or 21–24 years (emerging adults), childless, not currently pregnant (for men, partner not pregnant) or trying to conceive, presumed fertile and intending to have a child in the future. Of the 255 invited, 208 ( n = 93 adolescents, n = 115 emerging adults) participated. The FertiEduc group received 'A Guide to Fertility', four online pages of information about fertility topics (e.g. 'When are men and women most fertile?') and the Control group received four online pages from the National Health Service (NHS) pregnancy booklet 'Baby Bump and Beyond'. Participants completed a questionnaire (fertility knowledge, perceived threat of infertility, anxiety, physical stress and fertility plans, moderators) prior to and after the provision of information. Mixed factorial analysis of variance was used to examine the effects of information provision and hierarchical multiple regression to assess potential moderators of knowledge. MAIN RESULTS AND THE ROLE OF CHANCE: The FertiEduc and Control groups were equivalent on age, gender, disability, relationship status and orientation at baseline. Results showed that fertility information significantly increased fertility knowledge for emerging adults only ( P < 0.001) and threat of infertility for emerging adults and adolescents ( P = 0.05). The moderators were not significant. Participation in the study was associated with an increase in feelings of anxiety but a decrease in physical stress reactions. Adolescents had more optimal fertility plans compared to emerging adults due to being younger. LIMITATIONS, REASONS FOR CAUTION: This was an experimental study on a self-selected sample of men and women from selected educational institutions and only short term effects of information were studied. WIDER IMPLICATIONS OF THE FINDINGS: Provision of fertility information can have benefits (increased fertility knowledge) but also costs (increase potential threat of infertility). Adolescents find fertility information positive but do not learn from it. Fertility education should be tailored according to age groups and created to minimise negative effects. Longitudinal examination of the effects of fertility information in multi-centre studies is warranted and should include measures of perceived threat of infertility. STUDY FUNDING/COMPETING INTEREST(S): Cardiff University funded this research. All authors have no conflicts of interest to declare.